Greening existing buildings - Yudelson, Jerry (McGraw-Hill's GreenSource series, 2010)
This GreenSource guide explains how to transform existing buildings into more energy-efficient, resource-conserving green buildings. The book provides a clear process that guides you, step-by-step, through each phase of moving building operations and maintenance toward the goal of a green-certified building. Greening Existing Buildings features proven technologies and operating methods, and shows building owners and facility managers how to green buildings in a cost-effective way. This practical and insightful resource highlights the ten best practices for greening existing buildings, and includes more than 25 case studies of successful implementations and 35 insightful interviews with industry experts and building owners and managers.